Pengembangan media pembelajaran interaktif dengan pendekatan contextual teaching and learning pada materi matriks di Madrasah Aliyah Negeri 2 Model Medan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The purpose of this study was to determine: Is interactive learning media with the Contextual Teaching and Learning (CTL) approach to the matrix material in Madrasah Aliyah Negeri 2 Model Medan. The development model carried out in this study is the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The material in this research is matrix operations (including matrix addition, matrix subtraction, scalar multiplication, and matrix multiplication). Based on the media trial stage the media assessment stage by media experts has a rating of 4.39 and the media assessment by the material expert has an assessment of 3.62. So the average rating of media and material experts is 4.00. Whereas at the implementation stage of media assessment by the mathematics teacher of class XI it has a 4.00 rating and the media assessment by students has a value of 4.49. So the average media assessment by teachers and students is 4.25. So that the results of the evaluation of the development by media experts and data analysis experts have good qualifications. Whereas the results of the evaluation of the quality of the media by teachers and students obtained from the implementation stage were stated to have very good qualifications
Keywords: interactive learning media; contextual teaching and learning (CTL); matrix